2015
DOI: 10.3109/00952990.2015.1050497
|View full text |Cite
|
Sign up to set email alerts
|

Classification of alcohol use disorders among nightclub patrons: associations between high-risk groups, sociodemographic factors and illicit drug use

Abstract: Patrons of nightclubs show higher prevalence rates for any alcohol use disorders than the general population. Patrons could benefit from governmental brief intervention or referral to treatment for alcohol used disorders disclosed in nightclubs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
2
5
1
Order By: Relevance
“…The finding of this study was in line with a study carried out in Ethiopia, 21% [ 33 ], Dharan town, 25.8% [ 16 ], and Chitwan District of Nepal 23.8% [ 18 ]. However, the finding of the current study was lower than a study conducted in Brazil 50% [ 15 ], and Nigeria 39.5% [ 19 ].…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The finding of this study was in line with a study carried out in Ethiopia, 21% [ 33 ], Dharan town, 25.8% [ 16 ], and Chitwan District of Nepal 23.8% [ 18 ]. However, the finding of the current study was lower than a study conducted in Brazil 50% [ 15 ], and Nigeria 39.5% [ 19 ].…”
Section: Discussioncontrasting
confidence: 95%
“…Our study also identified male gender had a statistically significant positive correlation with alcohol use disorder (AOR = 4.34, 95 CI; 2.800, 6.743). This finding is supported by studies done in India [ 44 ], Brazil [ 14 , 15 ], and other parts of Ethiopia [ 22 , 32 ]. Heavy drinking is mostly occurred in men compared with women and biological differences among the two genders might be contributing to the discrepancy.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…When considered in the context of the drinking population, the prevalence of a likely AUD was 44%. This figure is close to that reported (almost 50%) that similarly used AUDIT, in a high-prevalence alcohol use setting (nightclubs) in Brazil in 2015 [ 24 ]. However, compared with figures from the general population, the prevalence of likely AUD reported in the study being reported was high.…”
Section: Discussionsupporting
confidence: 87%
“…The data used in this study originated from a website survey 26 carried out to diagnose drug use and other risk behaviors among party goers in the city of São Paulo, Brazil, in 2013 27 29 . In this study, nightclubs were defined as any establishment that presented control of entry and exit, sale of alcoholic beverages, and dance floor.…”
Section: Methodsmentioning
confidence: 99%